Genetic variation in PNPLA3 confers susceptibility to nonalcoholic fatty liver disease - Romeo, Stefano; Kozlitina, Julia; Xing, Chao; Pertsemlidis, Alexander; Cox, David; Pennacchio, Len A; Boerwinkle, Eric; Cohen, Jonathan C; Hobbs, Helen H (Nature genetics, 2008)
Helen Hobbs and colleagues report an association between coding variation in PNPLA3 and susceptibility to nonalcoholic fatty liver disease. The associated alleles vary in frequency among Hispanics, African Americans and European Americans and contribute to differences in disease prevalence among these ancestry groups. Nonalcoholic fatty liver disease (NAFLD) is a burgeoning health problem of unknown etiology that varies in prevalence among ancestry groups. To identify genetic variants contributing to differences in hepatic fat content, we carried out a genome-wide association scan of nonsynonymous sequence variations ( n = 9,229) in a population comprising Hispanic, African American and European American individuals. An allele in PNPLA3 (rs738409[G], encoding I148M) was strongly associated with increased hepatic fat levels ( P = 5.9 × 10 −10 ) and with hepatic inflammation ( P = 3.7 × 10 −4 ). The allele was most common in Hispanics, the group most susceptible to NAFLD; hepatic fat content was more than twofold higher in PNPLA3 rs738409[G] homozygotes than in noncarriers. Resequencing revealed another allele of PNPLA3 (rs6006460[T], encoding S453I) that was associated with lower hepatic fat content in African Americans, the group at lowest risk of NAFLD. Thus, variation in PNPLA3 contributes to ancestry-related and inter-individual differences in hepatic fat content and susceptibility to NAFLD.